Unpacking the objectives and assumptions underpinning European aquaculture - Ertör, Irmak; Ortega-Cerdà, Miquel (Environmental Politics, 2017)
Increasing demand for seafood and the lack of growth of capture fisheries have boosted aquaculture growth worldwide. However, European aquaculture has been stagnating over the past decade, and European public authorities have been developing policies and strategies in efforts to reverse this. Aquaculture discourses in the European Union, based on 34 policy, planning, and strategy documents, are examined and a discourse analysis conducted following Bacchi's WPR (What is the Problem Represented to be?) approach. How the problems in these discourses are represented, the tensions among main objectives, and the implicit assumptions are unveiled, and discussed employing a Polanyian theoretical framework. Taking these assumptions for granted leads to a disembedded understanding of aquaculture, and facilitates the privatization of aquatic space and resources. The analysis contributes to the literature establishing the link between the expansion of aquaculture and the enclosure of aquatic resources and enriches environmental and political debates on European aquaculture.
Environmental Science
Keywords: Europe; European Union law; aquaculture; aquatic resources; discourse analysis; enclosures; environmental politics; fisheries; fishery policy; government policy; privatization

CSR as a legitimatizing tool in carbon market: Evidence from Latin America’s Clean Development Mechanism - Benites-Lazaro, L.l.; Mello-Théry, N.A. (Journal of Cleaner Production, 2017)
Clean Development Mechanism (CDM) has incorporated sustainable development as one of their objectives. This objective gives companies an increasing motivation to contribute to sustainable development through their corporate social responsibility (CSR). However, perceived profitability of companies with carbon commodification were negatively associated with CDM projects. This paper aims to identify CSR activities in CDM in three Latin American countries, namely, Brazil, Mexico, and Peru and understand the drivers behind of these CSR initiatives. The study is based on the evaluation of 593 projects registered and Polanyi’s theory. We identified some CSR activities corresponding to the social, environmental and economic indicators in the three countries. This is not to say that all CDM developers are acting in a socially responsible manner. Certain CSR activities in most of the cases were implemented as a way to legitimize and as a means to achieve social acceptance.
Environmental Studies; Sustainability Studies
Keywords: CSR; Latin America; carbon dioxide mitigation; clean development mechanism; corporate legitimacy; corporate social responsibility; double movement; double-movement; economic aspects; embeddedness; emission control; social acceptance; social responsibility of business